Analysis of Ability to Pay and Willingness to Pay PBPU Participants Who Are In Arrears of National Health Insurance Contributions in Samarinda Ulu District - Nur Asiza; Muhammad Rafli Aidillah; Muhammad Henry Gunawan (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2022)
The implementation of the National Health Insurance program-Healthy Indonesia Card (JKN-KIS) in Indonesia is far from the goal. This study seeks to find out through an analysis of the ability and willingness to pay BPJS Kesehatan participants for participants Non-wage earners in the Samarinda Ulu District of Samarinda City. This type of research is an analytical survey with a cross-sectional research design, that is, research where data is collected only once to answer research problems. The population of this study was BPJS Kesehatan participants in the Non-Wage Earner group of 553 so that the study sample was 227 Data collection using a research questionnaire, then analyzed the collected data using bivariate analysis. Payment of dues for non-wage earners in Samarinda Ulu sub-district of Samarinda City is in a fairly good position even though in this case the level of consumptive community is high. Unable to pay is caused by some participants with low incomes and high consumptive rates